1995
DOI: 10.1006/viro.1995.1571
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Carbohydrate Addition Site on the Hemagglutinin Protein of a Highly Pathogenic H7 Subtype Avian Influenza Virus

Abstract: The highly pathogenic (HP) avian influenza isolate, A/Fowl/Victoria/76 (H7N7), contains two naturally occurring hemagglutinin (HA) variants. The two hemagglutinin proteins differ only in the possession of a potential asparagine-linked glycosylation site at amino acid position 188-190, which is near the proposed receptor binding region of the HA. Expanded virus plaques which possess the addition site exhibit more slowly migrating HA1 subunits and are significantly more lethal in chickens than those which lack t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…We speculate the glycosylation may improve virus receptor binding and infectivity in eggs based on similar findings reported for the HPAI virus A/Netherlands/219/2003 (H7N7) in which glycosylation at N133 increased its binding affinity to avian-type ␣2,3-linked sialosides (45). It was also reported that glycosylation at HA position 188 (H3# position 197) near the receptor binding site increased the virulence of an avian H7N7 strain in chicken (46). In contrast, the loss of a glycosylation site at HA position 133 of human H3N2 viruses is associated with better viral growth in MDCK cells (47).…”
Section: Discussionsupporting
confidence: 74%
“…We speculate the glycosylation may improve virus receptor binding and infectivity in eggs based on similar findings reported for the HPAI virus A/Netherlands/219/2003 (H7N7) in which glycosylation at N133 increased its binding affinity to avian-type ␣2,3-linked sialosides (45). It was also reported that glycosylation at HA position 188 (H3# position 197) near the receptor binding site increased the virulence of an avian H7N7 strain in chicken (46). In contrast, the loss of a glycosylation site at HA position 133 of human H3N2 viruses is associated with better viral growth in MDCK cells (47).…”
Section: Discussionsupporting
confidence: 74%
“…Mutations in HA and NA may be important also, because these genes are determinants of the host range of AIV. The addition of a potential N-linked glycosylation site at position 141 in HA may be of importance because changes near the receptor-binding site or at the tip of HA have been implicated in determining the pathogenic properties of H7N7 AIV (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Steric hindrance by a glycan adjacent to the receptorbinding site may therefore be a determinant of receptor specificity. Finally, the number and structure of N-glycans neighboring the receptor-binding pocket have been suggested to determine the host range and pathogenicity of influenza viruses (6,10,29). In view of these findings, it will now be interesting to employ our panel of recombinant viruses to elucidate the contributions of individual HA tip glycans to tissue tropism and host range.…”
Section: Discussionmentioning
confidence: 99%